Productivity and its relation to business management in Peruvian companies - Niño, Emilio Wilmer Barreto; Mejia, Percy Junior Castro; Velarde, Raúl Navarrete; Coronado, Grecy Yanina Becerra; Urrutia, Carlos William Atalaya; Montes, Mercedes Fátima Benites; Tassara, Pedro Demetrio Reyes; Arredondo, José Luis Ángelo; Delgado, Nelly Alicia Guevara (Edelweiss Applied Science and Technology, 2025)
This study sought to determine the relationship between productivity and Business Management in Peruvian companies. The methodology included a quantitative approach, applied type, non-experimental design, correlational and cross-sectional scope; in addition to having a sample of 50 employees to whom two questionnaires were applied seeking to evaluate their Business Management practices and the relationship it has within productivity. Among the results, Spearman’s Rho correlation coefficient was applied to determine the existence or not of a relationship between the variables "productivity" and "Business Management" as well as the dimensions of the variable "Business Management", it was obtained (1) the existence of a considerable positive correlation (r=0.723) and a significance level of less than 5% between both variables, (2) a considerable positive correlation (r=0.670) and a significance level of less than 5% between effectiveness and Business Management, (3) a considerable positive correlation (r=0.636) and a significance level of less than 5% between efficiency and Business Management and (4) a very strong positive correlation (r=0.853) and a significance level of less than 5% between innovation and Business Management. The conclusion is that those companies that prioritize effectiveness, efficiency and promote innovation within their business management are more productive and competitive in the market; furthermore, this study offers a solid platform for future research and for the development of strategies that promote productivity and business success in the Peruvian context.